Laboratory evaluation of the influence of decentration and pupil size on the optical performance of a monofocal, bifocal, and trifocal intraocular lens - Tandogan, Tamer; Son, Hyeck Soo; Choi, Chul Y.; Knorz, Michael C.; Auffarth, Gerd U.; Khoramnia, Ramin (Journal of refractive surgery, 2017)
Journal of Refractive Surgery | PURPOSE:To assess the influence of decentration and aperture size on the optical quality of different intraocular lenses (IOLs) of the same material, body design, and refractive power using standardized optical bench testing.METHODS:Using an optical bench set-up, an aspheric monofocal (CT ASPHINA 409M; Carl Zeiss Meditec, Jena, Germany), an aspheric diffractive bifocal (AT LISA 809M; Carl Zeiss